The Impact of Domestic Violence on Women’s Professional Competence And Organisational Performance - Noorashikin, Md Rashid; Helen Tan, Siew Hong; Roshazlizawati, Mohd Nor (2023)
This study examined the impact of domestic violence in marriage against career women with children, and the effect of experiences on their professional competence as well as overall career performance. Domestic violence relationship is considered an issue of epidemic proportions in many parts of the world including Malaysia. Studies show that women generally are very cautious to discuss matters that might attract any negative perception onto themselves or their family. Despite the increasing recognition that women need additional structural support in their professional lives. This study employs qualitative research method and the preliminary findings suggest that women prefer to share stories with others; rely on trusted family and friends for support, and lodge police reports as well as keep to themselves, usually suffering in silence instead of seeking support from the organisational structure. The findings are part of a larger research on how domestic violence impact women’s professional competence at the workplace. The potential larger implication domestic abuse involving professional women and the potential overall effect on the organisational performance is also explored. Recommendations for future research and how the findings contribute to the effort to improve lives for women which is enshrined under Sustainable Development Goal 5 are also discussed.